PENGARUH VARIASI KOMPOSISI KOMPOSIT BERBAHAN GYPSUM, SERAT IJUK POHON AREN DAN RESIN POLYESTER TERHADAP KEMAMPUAN MEREDAM SUARA - Idris, Idris; Mangalla, Lukas Kano; Sudia, Budiman (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
Sound pollution from noise is a classic problem in Indonesia. This noise can be reduced by using an acoustic damper. The composite material made from coconut fiber and matrix is an alternative to environmentallyfriendly acoustic damper material because it utilizes agricultural waste material. this research has been made of fiberr matrix composite, gypsum powder with polyester resin. To increase the strength of coconutfiber first soaked in 2% NaOH solution for 1 hour. The composites are then tested for the value of the sound absorption coefficient (????), the composite damping test is performed on the kundts tube impedance tool in the speaker, amplifier, power supplay, laptop/smartphone, oscilloscope, sound lever meter with input frequency 600,800,1000 Hz. The test result of the value of Noice Absorption Coefficient (NAC) of all specimens of polyester resin composite test in fiber reinforcement fiber and gypsum powder has the highest absorption coefficient (????)=0.358316 at 30: 20: 50% fiber fraction with 1000 Hz frequency. As for the lowest sound absorption results (????)=0.351631 with fiber volume fraction 20: 30: 50% with a frequency of 600 Hz. In the general whole specimens can be made as a damper because it has a value of sound absorption coefficient >0,3.Keywords: composite, gypsum, fibers, polyester and NAC.